Efficacy and safety of glycyrrhizic acid preparation treating comorbid liver injury in COVID-19: A systematic review - Liu, Xu; Tian, Xia; Ma, Zhipeng; Chen, Jiali; Huang, Qingsong; Gao, Peiyang; Zhang, Chuantao (Frontiers in Pharmacology, 2022)
Backgrounds: No specific drug for COVID-19 has been found, and many studies have found that different degrees of liver injury often occurred after infection with COVID-19. Glycyrrhizic acid preparation (GAP) has been frequently used clinically, often combined with conventional treatments such as antiviral therapy, to improve the prognosis of COVID-19 and patients’ liver function. Aims: To critically review and analyze clinical evidence on the efficacy and safety of GAP in the treatment of COVID-19 alone and COVID-19 with comorbid liver injury. Methods: A systematic literature review was performed following a sensitive searching strategy that examines all articles published in “WHO COVID-19 Research Database”, “Cochrane Library”, “VIP”, “CNKI”, “Wanfang” and “CBM” from 2020 to July 2022. Articles were evaluated by peer reviewers and used Joanna Briggs Institute (JBI) critical appraisal tools to complete the assessment of the risk of bias. Results: Ten clinical studies were finally included, involving 598 patients with COVID-19, of whom 189 were confirmed to be with comorbid liver injury. The main GAPs used are diammonium glycyrrhizinate and magnesium isoglycyrrhizinate, which have shown efficacy in improving liver function, inhibiting inflammation, and enhancing immunity. We are still seeking more related research. Conclusions: Glycyrrhizic acid preparations (mainly diammonium glycyrrhizinate and magnesium isoglycyrrhizinate) have a considerable clinical effect on improving liver function in patients with COVID-19 alone or with comorbid liver injury. Further studies on the use of GAP in the treatment of COVID-19 with comorbid liver injury and its mechanism are still needed.